Digital Delivery of Meditative Movement Training Improved Health of Cigarette-Smoke-Exposed Subjects - Peter Payne; Steven Fiering; David Zava; Thomas J. Gould; Anthony Brown; Paul Hage; Carole Gaudet; Mardi Crane-Godreau (Frontiers Media S.A., 2018)
Many FA who flew prior to the ban on smoking in commercial aircraft exhibit an unusual pattern of long-term pulmonary dysfunction. This randomized controlled study tested the hypothesis that digitally delivered meditative movement (MM) training improves chronic obstructive pulmonary disease (COPD)-related symptoms in flight attendants (FA) who were exposed to second-hand cigarette smoke (SHCS) while flying. Phase I of this two-phase clinical trial was a single-arm non-randomized pilot study that developed and tested methods for MM intervention; we now report on Phase II, a randomized controlled trial comparing MM to a control group of similar FA receiving health education (HE) videos. Primary outcomes were the 6-min walk test and blood levels of high sensitivity C-reactive protein (hs-CRP). Pulmonary, cardiovascular, autonomic and affective measures were also taken. There were significant improvements in the 6-min walk test, the Multidimensional Assessment of Interoceptive Awareness (MAIA) score, and the COPD Assessment Test. Non-significant trends were observed for increased dehydroepiandrosterone sulfate (DHEAS) levels, decreased anxiety scores and reduced blood hs-CRP levels, and increased peak expiratory flow (PEF). In a Survey Monkey questionnaire, 81% of participants who completed pre and post-testing expressed mild to strong positive opinions of the study contents, delivery, or impact, while 16% expressed mild negative opinions. Over the course of the year including the study, participant adoption of the MM practices showed a significant and moderately large correlation with overall health improvement; Pearson's R = 0.62, p < 0.005. These results support the hypothesized benefits of video-based MM training for this population. No adverse effects were reported.Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT02612389